1973
DOI: 10.1021/jf60190a023
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the rate of formation of nitrosomorpholine from morpholine and nitrite. II. Rate enhancement in frozen solution

Abstract: The reaction of nitrite and morpholine as a model of a nitrosation reaction has been studied in frozen model systems and in frozen milk. The rate was considerably enhanced in frozen systems compared to that expected for a supercooled solution at the same temperature. The degree of enhancement appeared to be a function of overall solute concentration, which in turn controls the amount of unfrozen solution at any temperature. Because this type of nitrosation reaction is third-order, a threefold concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Several studies on the kinetics of nitrosamine formation have been reported. [109][110][111][112][113] The mechanisms of these reactions and the atmospheric importance of this formation pathway are, however, quite uncertain and even the reaction order is not clear. Keefer and Roller 114 reported that the nitrosation of secondary amines takes place even in neutral and basic media, and that the reaction is catalysed by formaldehyde.…”
mentioning
confidence: 99%
“…Several studies on the kinetics of nitrosamine formation have been reported. [109][110][111][112][113] The mechanisms of these reactions and the atmospheric importance of this formation pathway are, however, quite uncertain and even the reaction order is not clear. Keefer and Roller 114 reported that the nitrosation of secondary amines takes place even in neutral and basic media, and that the reaction is catalysed by formaldehyde.…”
mentioning
confidence: 99%
“…It is not an uncommon phenomenon that reaction rates in ice are faster than those in solution. In most cases, the freeze-concentration into unfrozen solution in ice (when each small region of unfrozen solution existing in ice is indicated, we use the term “micro-pocket”) is the main reason for the increase in reaction rate. Pincock reported an acceleration theory for the freeze-concentration effect .…”
Section: Introductionmentioning
confidence: 99%
“…Rates of chemical reactions in aqueous solution are generally suppressed with decreasing temperature. However, some reactions are accelerated in ice despite being at lower temperatures than in solution. The acceleration of reactions in ice has been studied actively since the 1960s in the field of food chemistry and biochemistry, where acceleration mechanisms were reported. Pincock reviewed the reactions in frozen systems 1 and concluded that freeze-concentration in an unfrozen solution of ice was the only cause of acceleration in such systems.…”
Section: Introductionmentioning
confidence: 99%